Power yoga strength, sweat, and spirit - Cullis, Leah 1980- (Human Kinetics, 2019)
Expand your energy and raise your sense of personal power with yoga, the athletic and dynamic style of yoga that delivers high intensity and quick results. In Power Yoga: Strength, Sweat, and Spirit, you will learn the poses, practices, and philosophy of this fitness- and focus-boosting training method to strengthen your body and awaken your spirit. This potent practice is a complete workout on its own, but it also offers tremendous benefits when combined with other workouts and sports. In addition to physical strength, stamina, and flexibility, the dynamic movements of power yoga challenge you to develop focus, balance, and purpose that extend to life beyond the yoga mat. Dozens of warm-up, power, peak, and cool-down poses are presented in full color, and adaptations to modify or intensify each pose allow you to customize your practice for maximum effectiveness and safety. Sequences ranging from 5 to 60 minutes - including specific sequences for running, cycling, team sports, and high-intensity activities- offer options that match your goal of lifestyle, and the 28-day plan can be adjusted into a plan that works for you, based on the results you want. Power Yoga: Strength, Sweat, and Spirit is your vehicle for creating extraordinary physical and spiritual results that you will notice quickly and be able to maintain for a lifetime. Become your most powerful self with power yoga.